Measuring the impact of a burns school reintegration programme on the time taken to return to school: A multi-disciplinary team intervention for children returning to school after a significant burn injury. Issue 4 (June 2015) - Arshad, Sira N.; Gaskell, Sarah L.; Baker, Charlotte; Ellis, Nicola; Potts, Jennie; Coucill, Theresa; Ryan, Lynn; Smith, Jan; Nixon, Anna; Greaves, Kate; Monk, Rebecca; Shelmerdine, Teresa; et al.
Abstract Introduction Returning to school can be a major step for burn-injured children, their family, and staff and pupils at the receiving school. Previous literature has recognised the difficulties children may face after a significant injury and factors that may influence a successful reintegration. Aim A regional paediatric burns service recognised that some patients were experiencing difficulties in returning to school. A baseline audit confirmed this and suggested factors that hindered or facilitated this process, initiating the development of a school reintegration programme (SRP). Since the programme's development in 2009, it has been audited annually. The aim of this paper was to evaluate the impact of the SRP by presenting data from the 2009 to 2011 audits. Method For the baseline audit, the burn care team gathered information from clinical records (age, gender, total body surface area burned (TBSA), skin grafting and length of stay) and telephone interviews with parents and teachers of the school returners. For the re-audits, the same information was gathered from clinical records and feedback questionnaires. Results Since its introduction, the mean length of time from discharge to return to school has dropped annually for those that opted into the programme, when compared to the baseline by 62.3% (53 days to 20 days). Thematic analysis highlights positive responses to the programme from all involved. Increased awareness and feeling supported were amongst the main themes to emerge. Conclusions Returning to school after a significant burn injury can be challenging for all involved, but we hypothesise that outreach interventions in schools by burns services can have a positive impact on the time it takes children to successfully reintegrate.